Communicating Uncertain Science to the Public: How Amount and Source of Uncertainty Impact Fatalism, Backlash, and Overload. Issue 1 (12th March 2016) - Jensen, Jakob D.; Pokharel, Manusheela; Scherr, Courtney L.; King, Andy J.; Brown, Natasha; Jones, Christina
Abstract : Public dissemination of scientific research often focuses on the finding (e.g., nanobombs kill lung cancer) rather than the uncertainty/limitations (e.g., in mice). Adults ( n = 880) participated in an experiment where they read a manipulated news report about cancer research (a) that contained either low or high uncertainty (b) that was attributed to the scientists responsible for the research (disclosure condition) or an unaffiliated scientist (dueling condition). Compared to the dueling condition, the disclosure condition triggered less prevention‐focused cancer fatalism and nutritional backlash.